The influence of smoking on oral neutrophils and matrix metalloproteinase-8 in periodontitis patients before and after nonsurgical treatment - Hang T. Do; Thuy T. Nguyen; Thuy L. Vo; Nam C-N. Huynh; Anh T.K. Nguyen (Elsevier, 2023)
Objective: To evaluate and compare the oral neutrophil numbers (ONN) in saliva, the level of matrix metalloproteinase-8 (MMP-8) in gingival crevicular fluid (GCF) and the periodontal parameters in smokers versus non-smokers with periodontitis, before and after nonsurgical periodontal treatment (NSPT). Materials and method: 40 chronic periodontitis patients including 20 smokers and 20 non-smokers were enrolled in this quasi-experimental study. All patients were received the NSPT included instructing oral hygiene, scaling and root planing. At baseline (T0) and after NSPT 1 month (T1) and 3 months (T3), all patients were assessed for salivary ONN, GCF MMP-8, and clinical parameters like plaque index (PlI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment loss (CAL). The differences between the two groups were analyzed using the independent sample t-test and the Mann-Whitney U test; and the differences between T0, T1 and T3 of each group were analyzed with paired-samples t-test and Wilcoxon signed-rank test. The level of significance was set at 0.05. Results: The ONN was significantly less in smokers than in non-smokers although there was no significant difference in other parameters between the two groups at baseline (p > 0.05). All clinical periodontal parameters reduced significantly after 1 month and 3 months of NSPT in both groups (p < 0.01). PPD of non-smokers was significantly lower than those of smokers at T1 and T3. ONN and MMP-8 level showed a significant decrease in non-smoking subjects, while there was no significant difference in smoking ones after NSPT (T1 and T3). At 1 month after treatment, ONN tended to reduce in non-smokers whereas to increase in smokers significantly. Conclusion: Smoking reduced ONN, impaired treatment effect in reducing PPD, and changed the MMP-8 level in gingival crevicular fluid to NSPT. Trial registration: Identifier NCT04974502 in CLinicalTrials.gov